APLIKASI TRICHODERMA UNTUK MENINGKATKAN PRODUKTIVITAS SORGUM VARIETAS NUMBU PADA KONDISI PEMBERIAN PUPUK MINIMAL - Retno Dwi Andayani (Universitas Tribhuwana Tunggadewi, 2021)
Sorghum is a suitable crop grown in dry and nutrient-poor areas. So it is suitable to be developed in dry and marginal land areas. However, in the cultivation of sorghum on dry land and lack of nutrients, it still needs the effort to increase the yield. This study aimed was to determine the response of sorghum plants to the application of Trichoderma sp. and fertilizer dosage. Treatments tested in this study were with the first factor being the application of Trichoderma and the second factor being the fertilizer dose of 50%, 40%, 30%. 20%, 10% and 0%. The results showed that the treatment has no interaction between Trichoderma application and fertilizer dosage. However, the fertilizer dose had a significant effect on all observation parameters. A fertilizer dose of 40% provides the most effective and efficient results to support the growth and production of sorghum plants.